PRODUKSI FILM DOKUMENTER “SPIRIT OF JAVA GAMELAN” - Firdaus; Wijaksono, Dimas Satrio (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2022)
Indonesian is a nation that has a diversity of cultures. One of the performing arts is yogyakarta gamelan festival. Yogyakarta gamelan festival is a festival that is held regularly for 25 years and on an international scale to accommodate the meeting of players and lovers of gamelan music around the world. The final task work in the form of a documenter film entitled "Spirit of Java Gamelan"aims to find out how the Yogyakarta Gamelan Festival event can be carried out consistently for 26 years. This documenter film is based on theory mass communication, persuasive communication, film, film documenter, cinematography, sound order, lighting and culture. Data collection uses methods of research, observation, library studies and interviews. The data was collected and then analyzed to be used in the form of a 17-minute documentary, this documenter tells about how Yogyakarta Gamelan Festival event can be held consistently for 26 years. Key Words: Culture; Film Documenter; Yogyakarta Gamelan Festival